Pembuatan animasi 3 dimensi “Ramadhan di Ma’had": Menyadarkan makna puasa dan syukur menggunakan metode pose to pose - Zaidan, Muchammad Alif; Nugroho, Fresy; Karami, Ahmad Fahmi (Maliki Interdisciplinary Journal, 2023)
3D animation has transformed the entertainment, education, and marketing industries with its ability to create objects and characters in immersive virtual environments. With the advancement of computer technology, the process of creating 3D animation is increasingly efficient and realistic, involving complex software and techniques. The integration of high graphic technology, visual arts, and design concepts has resulted in immersive and immersive experiences for audiences around the world. This study aims to discuss the creation of a 3D animation "Ramadan in Ma’had: Awakening the Meaning of Fasting and Gratitude" using the Pose to Pose method, with the aim of conveying messages about the importance of fasting and gratitude during Ramadan. The Pose to Pose method is used in the animation creation process, which involves creating a main frame (pose) which is then filled with smooth transitions (in-between) to create a realistic and interesting animation. The result is a 3D animation that depicts the Ramadan experience in Ma’had by evoking emotions and increasing understanding of the meaning of fasting and gratitude.